The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/app.47891
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and improved mechanical properties of twin‐mesogenic epoxy thermosets using siloxane spacers with different lengths

Abstract: A series of twin-mesogenic epoxy resins with siloxane (di-, tri-, and tetra-siloxane) chain spacers of different lengths were successfully synthesized. Results showed that the melting point of the twin-mesogenic epoxy monomers decrease by more than 50 C due to the change of siloxane spacer length. In particular, the tri-and tetra-incorporated siloxane twin-mesogenic epoxy monomers showed a liquid crystalline (LC) phase below 100 C during the cooling process. Epoxy thermosets with isotropic and smectic (S m ) L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Furthermore, the fracture energy calculated from the area under the stress-strain curves is employed to study the toughness of EP composites. 30 The fracture energy of ATCG-PVP/EP-0.2 composite is increased to 3.6 kJ m À2 (56.5% higher than the corresponding value for pure EP), indicating the remarkable improvement in toughness. Dose the PVP surfactant play the role of toughening agent in EP composites?…”
Section: Performance Of Ep Compositesmentioning
confidence: 91%
“…Furthermore, the fracture energy calculated from the area under the stress-strain curves is employed to study the toughness of EP composites. 30 The fracture energy of ATCG-PVP/EP-0.2 composite is increased to 3.6 kJ m À2 (56.5% higher than the corresponding value for pure EP), indicating the remarkable improvement in toughness. Dose the PVP surfactant play the role of toughening agent in EP composites?…”
Section: Performance Of Ep Compositesmentioning
confidence: 91%
“…This is attributed to the induced molecular orientation in the networked epoxy polymer chains. Frequently used mesogenic backbone structures include biphenyl, 4–7 terphenyl, 8 stilbene, 9–20 azomethine, 21–36 ester, 37–49 ketone, 50 and azo 51,52 . In an earlier study, we reported a remarkable improvement in both the thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 89%
“…This is attributed to the induced molecular orientation in the networked epoxy polymer chains. Frequently used mesogenic backbone structures include biphenyl, [4][5][6][7] terphenyl, 8 stilbene, [9][10][11][12][13][14][15][16][17][18][19][20] azomethine, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ester, [37][38][39][40][41][42][43][44][45][46][47][48][49] ketone, 50 and azo. 51,52 In an earlier study, we reported a remarkable improvement in both the thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Mesogenic groups and flexible chains exist between epoxy groups [ 19 ]. In addition, the twin mesogenic epoxy monomer has a structure in which a flexible chain exists between the mesogenic groups [ 24 ]. The properties of LCE tend to depend on the flexibility of the mesogenic group and spacer attached to the epoxy group; therefore, the structure and properties of the mesogenic group are important factors affecting the thermal conductivity of LCE [ 25 , 26 ].…”
Section: Molecular Design Of Liquid Crystalline Epoxiesmentioning
confidence: 99%